ASSESSMENT OF PARAMETERS OF WINTER SOFT WHEAT ADAPTABILITY - I. A. Rybas; D. M. Marchenko; E. I. Nekrasov; M. M. Ivanisov; T. A. Grichanikova; I. V. Romanyukina (Зерновое хозяйство России, 2018)
During the years of study (2015–2017) there were considered and studied parameters of adaptability of winter soft wheat varieties sown after maize. As a result, the productivity of winter wheat ranged from 77.6 hwt/ha (the variety ‘Polina’) to 83.9 hwt/ha (the variety ‘Kaprizulya’). At a most the productivity varied through the years from 52.5 hwt/ha (the variety ‘Kapitan’) in 2016 to 108.2 hwt/ha (the variety ‘Kaprizulya’) in 2017. The main feature of breeding on adaptability is to control ecological plasticity and stability of the varieties in the breeding process. The varieties ‘Krasa Dona’ and ‘Kaprizulya’ having 1.0 regressive coefficient are considered to be ecologically adaptable. The varieties ‘Lidiya’, ‘Kapitan’, ‘Lilit’ and ‘Volnitsa’ having > 1.0 regressive coefficient are considered to be highly responsive. The varieties ‘Lilit’ and ‘Volny Don’ are characterized with stable genotype (σd2 tends to zero). The varieties ‘Polina’ and ‘Volny Don’ belong to the group of varieties with high indexes of homeostatism, breeding value and low coefficients of variations. The varieties ‘Polina’ and ‘Volny Don’ demonstrate high indexes of stress resistance with the lowest negative values of differences among minimum and maximum indexes of the trait. The varieties ‘Kaprizulya’, ‘Lilit’, ‘Krasa Dona’ and ‘Volny Don’ are found genetically flexible genotypes, as they possess high correspondence degree between the genotype and the environment. According to the parameters of adaptability there have been identified the varieties ‘Polina’ and ‘Volny Don’ with stability, breeding value, stress resistance and high productivity.